Capital structure choices, pension fund allocation decisions and the rational pricing of liability streams. (18th July 2022) - Martellini, Lionel; Milhau, Vincent
Abstract: This paper introduces an integrated asset-liability management model that allows for the joint quantitative analysis of capital structure choices, pension fund allocation decisions and rational pricing of liabilities. We confirm that capital structure decisions have a substantial impact on the value of pension claims, and we provide a quantitative assessment of the mispricing induced by the use of an arbitrary regulatory discount rate. We also present a quantitative assessment of the asset substitution effect implied by a change in the pension fund allocation to risky assets taking place after the corporate and pension obligation claims have been issued.